Faktor Pembentuk Resiliensi Remaja Dari Keluarga Broken Home di Desa Pucung Lor Kecamatan Kroya Kabupaten Cilacap - Khusnul Khotimah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
This study aims to describe the factors of forming adolescent resilience from broken home family in Pucung Lor Village, Kroya District, Cilacap District. Resilience is a person’s ability to adapt and survive even when a person faces a difficult situation. This research uses descriptive qualitative research type, and take the location in Pucung Lor Village, Kroya District, Cilacap District. The subjects of this study were 15 adolescents consisting of 9 (nine) female adolescents and 6 (six) men adolescents from broken home family in Pucung Lor village, Kroya District, Cilacap District. Data collection methods used by observation, interview, and documentation. Techniques used in conducting data analysis is data reduction, data presentation, and conclusion. The validity of the data performed to explain the data using source triangulation. The results showed that the factor of the resilience of adolescent in Pucung Lor village had a different factor on the resilience ability seen in adolescent condition from broken-home family experienced by each subject. Internal factors affecting adolescent resilience from broken home family in Pucung Lor village are dominantly seen in emotional regulation factor, impulse control, empathy, self-efficacy, and reaching out. While external factors are seen in family and social factors that dominate in adolescents from broken home family in Pucung Lor village in realizing its ability resilience.